O lazer nas aulas de Educação Física: construindo conhecimento com professores de Ensino Médio da FUNEC - Adriana Angélica Lobo Leite (2017)
The object of this research are the reflections and the experiences of leisure in the classes of Physical Education of the High School in Teaching Foundation of Contagem (FUNEC). The study discourses the possibilities of leisure experiences in Physical Education classes in order to identify how it are understood, treated and developed on them. The research was produced in two moments: first an investigation of the daily life of Physical Education classes, when a qualitative descriptive approach was adopted and the combination of bibliographical and observation research; In the second moment, interventions were made with the Physical Education teachers of three FUNEC schools, occasion that made possible knowledge production and intervention on the area alternatives. Among the products of this investigation are the dissertation and three technical products: a) a document to be delivered to FUNEC's presidency; B) a research project approved for 2017 (PIBIC-Jr); C) a blog. The research had as a principle to reflect on the leisure practices in the Physical Education classes of High School and to understand the development, appropriation and transformation of school and leisure practices. The study revealed that the intercession between Physical Education and leisure might be a means to sociocultural transformation, to reflection on the type of society we want to build and to produce a greater criticality on the social dictates that are imposed by the current capitalist system. It also revealed the importance of collective teaching work and the expansion of continuing education contexts within the school. Since leisure is an important dimension of youth experiences, this work has also made visible the need for attention to the numerous young students cultural manifestations of leisure